Early childhood bilingualism: Straddling the divide between Pseudoscience and evidence-based practice - Gozali, Imelda (Beyond Words, 2023)
Many parents in the English as a Foreign Language (EFL) context such as Indonesia might have held to the belief of the golden age for learning language, as evidenced by the proliferation of the so-called international preschools in which subjects are taught in English or Chinese. In the realm of language acquisition, this the younger the better belief is still debatable among the scholars in the field, with some demonstrating the success of childrens early exposure to foreign languages and others who dismissed it as a myth. Thus, this brief article set out to view the debate under the lens of philosophy, particularly that of Poppers pseudoscience perspective in order to decide whether early childhood bilingualism is pseudoscientific or an evidence-based practice. The article concludes that it might be too early to call early childhood bilingualism a myth, and proposes practical recommendations for parents with young children.